Novel products of reaction between K[PtCl3(eugenol)] and some pyridine’s derivatives - Cam Mai, Truong Thi; Dinh, Le Thi; Huy, Le Viet; Thanh Chi, Nguyen Thi (Vietnam Journal of Chemistry, 2017)
The interaction between K[PtCl3(Eug)] (M0) and either 4-carboxylpyridine (4-Cpy) or 4-methylpyridine (4-MePy) has been studied for the first time. The structures of unusual resulting complexes, namely [PtCl(Eug-1H)(4-CPy)] (M1), trans-[PtCl2(4-MePy)2] (M2), trans-[PtCl2(Eug)(4-MePy)] (M3) were determined by means of platinum analysis, IR, 1H NMR spectroscopy and single-crystal X-ray diffraction. In these complexes, the amines coordinate with Pt(II) via the N atom and eugenol (Eug) in M1, M3 coordinates with Pt(II) via ethylenic double bond of the allyl group. In M1, the deprotonated eugenol is bound up with Pt(II) not only at the C=Callyl but also at C atom of the benzene ring to generate the metallacyclic complex. M2 and M3 possess trans configuration. Keywords. Eugenol, platinum(II) complex, 4-carboxylpyridine, 4-methylpyridine.